Automated Observations of the Earthshine - P. R. Goode; S. Shoumko; E. Pallé; P. Montañés-Rodríguez (Advances in Astronomy)
The overall reflectance of sunlight from Earth is a fundamental parameter for climate studies. We have designed and implemented small aperture, remote control telescopes in Big Bear Solar Observatory in California and in Tenerife in the Canary Islands. These telescopes observe the earthshine to obtain a global mean terrestrial reflectance utilizing a coronagraph-like design for long exposures of the dark of the Moon and have internal moving parts in the optical train, which presented some design and control problems.